Design a Technique for Minimizing Unnecessary Handoff in Mobile Wireless Networks - Rahman, Md. Arafatur; Qusay, Medhat Salih; Mohamad Fadli, Zolkipli (2015)
Unnecessary handoff is one of the key issues in mobile wireless network, since it consumes the network’s resources that degrades the performance of the network. Handoff appears when the Receive Signal Strength (RSS) of a mobile node becomes below threshold value (i.e., an acceptable level of RSS for ensuring communication). Subsequently, the mobile node starts(AP) to keep continuing the communication. However, traditional handoff algorithm is not accurate due to only depend on the RSS. It is affected by many factors (e.g., shadowing, scattering,reflection, etc.) that initiate unnecessary handoff decision. In this paper, a new technique is proposed to mitigate the unnecessary handoff. The simulation result confirms the effectiveness of the proposal.